Description of the Growth of the Bacteria of Staphylococcus Aureus and Escherichia coli in Alternative Medium of Sunflower (Helianthus Annuus L.) - Yingjie Xu (Universitas Lampung, 2022)
The most used media for microbiological testing are nutrient agar because of their versatility. Nutrient Agar medium, meantime, is not cheap. This pushes researchers to find affordable, easily obtainable natural medium that have sources of nutrients for bacterial growth. One of them makes use of sunflower seeds, which have protein sources, raising the possibility that Sataphylococcus aureus and Escherichia coli can utilise them as a source of nourishment. The purpose of this study is to ascertain whether bacterial growth occurs and to assess the possibility of alternate media to sunflower seed agar as a medium for bacterial growth. The quadran streak method is being used in this descriptive investigation on the non-traditional media of sunflower seed agar and Nutrient Agar. Based on the research findings after observing the data, it was found that Escherichia coli can grow on sunflower seed agar as an alternative media, while Staphylococcus aureus cannot be grown because it is believed that sunflower seeds contain antimicrobial compounds like alkaloids, flavonoids, phytosterols, and tannins. The inference is that Escherichia coli can thrive on alternate media made of sunflower seed agar but Staphylococcus aureus cannot.